RNA sequencing analysis revealed differentially expressed genes and their functional annotation in porcine longissimus dorsi muscle affected by dietary lysine restriction - Hasan, Md. Shamimul; Wang, Ying; Feugang, Jean M.; Zhou, Huaijun; Liao, Shengfa F. (Frontiers in Veterinary Science, 2023)
The objective of this study was to investigate the effects of dietary lysine restriction on the global gene expression profile of skeletal muscle in growing pigs. Twelve crossbred (Yorkshire × Landrace) barrows (initial BW 22.6 ± 2.04 kg) were randomly assigned to two dietary treatments (LDD: a lysine-deficient diet; LAD: a lysine-adequate diet) according to a completely randomized experiment design (n = 6). After feeding for 8 weeks, skeletal muscle was sampled from the longissimus dorsi of individual pigs. The muscle total RNA was isolated and cDNA libraries were prepared for RNA sequencing (RNA-Seq) analysis. The RNA-Seq data obtained was then analyzed using the CLC Genomics Workbench to identify differentially expressed genes (DEGs). A total of 80 genes (padj ≤ 0.05) were differentially expressed in the longissimus dorsi muscle of the pigs fed LDD vs. LAD, of which 46 genes were downregulated and 34 genes were upregulated. Gene Ontology (GO) analysis of the DEGs (padj ≤ 0.05) for functional annotation identified those GO terms that are mostly associated with the molecular functions of structural molecules and metabolic enzymes (e.g., oxidoreductase and endopeptidase), biological process of acute-phase response, and amino acid metabolism including synthesis and degradation in the extracellular matrix region. Collectively, the results of this study have provided some novel insight regarding the molecular mechanisms of muscle growth that are associated with dietary lysine supply.